Dreams and visions : an interdisciplinary enquiry - Van Deusen, Nancy (Nancy Elizabeth) (Presenting the past (Leiden, Netherlands) ;, 2010)
Dreams and Visions have constituted an important topic and point of departure in the past; but also continue to play a present role in literature, political thought, economic theory, and in the arts. An essential historical topos, "Dreams and Visions"--The second in a series that projects past issues into the present--brings significant contributions from an interdisciplinary spectrum of standpoints in order to discover fresh insights. Perhaps this is the essence, in any case, of "Vision"--to discover new, fresh ways of conceptualizing a problem, topic, or historical enquir